„Gatemania” jako przykład tabloidyzacji śledztw dziennikarskich - Adamczyk, Wojciech (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The author of the paper analyzes the phenomenon of ‘gatemania’ in the mass media, paying particular attention to its influence on investigative journalism. Both the origins and evolution of this disturbing trend are discussed, beginning with William Lewis Safire. The author presents a broad range of definitions of the notion of ‘gatemania’, coined by the British journalist working for The Guardian, David Marsh. The paper enumerates a number of media scandals the media have referred to using the -gate suffix, ordering them by the three most frequent criteria. The relations between the stages of a classical model of muckraking and the components of a scandal are discussed, along with the elements that distinguish investigative journalism from tabloid-like journalism. In the opinion of the author, excessive use of the -gate suffix serves the purpose of the tabloidization of the message and is usually inadequate in relation to the event described; another reason for its use is to mislead readers, by implying that the articles are a result of investigative journalism.